2003
DOI: 10.1046/j.1460-9592.2003.t01-1-00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a New Active‐Fixation Lead in Transvenous Temporary Pacing from the Femoral Approach

Abstract: Temporary transvenous pacing is associated with a high incidence of complications with a substantial dislocation rate reported to occur in more than one-third of patients. This article describes a novel 3.5 Fr temporary pacing lead using active fixation in a consecutive series of 42 patients with prolonged (> or = 48 hours) temporary pacing. The dislocation rate was 4.8%, while in 7.1% of patients inappropriate pacing (more than a twofold increase of initial pacing threshold) was observed. The total procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…However, conventional transvenous temporary pacing using a passive or active pacing electrode is associated with substantial complications, including local infection, thrombosis, and a dislocation rate ranging from 10% to 37%, which imposes a definite risk for sudden cardiac death, particularly in patients without underlying rhythm 2,3,6,9 . In this respect, Rastan et al as well as de Cook and coworkers reported very promising data on a modified surgical approach of temporary pacing in patients with device infection using a permanent bipolar pacing lead, which was transcutaneously placed in the right ventricle and connected to an external pacing generator 4,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional transvenous temporary pacing using a passive or active pacing electrode is associated with substantial complications, including local infection, thrombosis, and a dislocation rate ranging from 10% to 37%, which imposes a definite risk for sudden cardiac death, particularly in patients without underlying rhythm 2,3,6,9 . In this respect, Rastan et al as well as de Cook and coworkers reported very promising data on a modified surgical approach of temporary pacing in patients with device infection using a permanent bipolar pacing lead, which was transcutaneously placed in the right ventricle and connected to an external pacing generator 4,10 …”
Section: Introductionmentioning
confidence: 99%
“…2,3,6,9 In this respect, Rastan et al as well as de Cook and coworkers re-ported very promising data on a modified surgical approach of temporary pacing in patients with device infection using a permanent bipolar pacing lead, which was transcutaneously placed in the right ventricle and connected to an external pacing generator. 4,10 The aim of the present prospective and controlled study was to evaluate the safety and efficiency of two different transvenous temporary pacing techniques using an active-fixation lead connected to an external pacing generator compared with a conventional passive-fixation pacing lead in critically ill patients with systemic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Temporary transvenous pacing with an active fixation of bipolar leads as bridging therapy has been used in the management of infected devices in pacemaker dependent patients [23,24]. This method of pacing was successfully used in the management of both pediatric and geriatric patients in a variety of clinical situations, with acceptable safety and low complication rates [25][26][27][28][29]. De Cock et al [25] and Pinto et al [27] used Medtronic 6416 active fixation lead while Jokhi et al [28] used a lead similar to the lead used by us.…”
Section: Discussionmentioning
confidence: 99%
“…The radiography on postoperative day 3 documents complete removal of the ICD system and an externalized lead for temporary VVI pacing (2b). temporary pacing systems [7]. All these approaches are associated with significant risks.…”
Section: Commentsmentioning
confidence: 99%
“…Lead displacements as well as infections are well known complications even for active-fixation temporary pacing leads, therefore these patients require monitoring on special care units [7]. The function of the externalized permanent pacemaker system as described above is supposed to be as safe as internal permanent pacemakers.…”
Section: Commentsmentioning
confidence: 99%